Effect of antioxidants on Saccharomyces cerevisiae mutants deficient in superoxide dismutases - Krasowska, A; Dziadkowiec, D; Łukaszewicz, M; Wojtowicz, K; Sigler, K (Folia microbiologica, 2003)
S. cerevisiae strain delta sodl lacking Cu,Zn-superoxide dismutase and delta sodl delta sod2 mutant lacking both Cu,Zn-SOD and Mn-superoxide dismutase displayed strongly reduced aerobic growth on glucose, glycerol and lactate; delta sod2 deletion had no effect on aerobic growth on glucose and largely precluded growth on glycerol and lactate. The oxygen-induced growth defects and their alleviation by antioxidants depended on growth conditions, in particular on oxygen supply to cells. Under strong aeration, vitamins A and E had a low effect, 100 mumol/L quercetin alleviated the growth defects of all three mutants while beta-carotene had no growth-restoring effect. The superoxide producer paraquat inhibited the aerobic growth of all three mutants in a concentration-dependent manner. Low concentrations of antioxidants had no effect on paraquat toxicity while higher concentrations supported the toxic effect of the agent.
Keywords: Antioxidants; Bacteriological Techniques; Phenotype; parciální tlak; bakteriologické techniky; Saccharomyces cerevisiae; superoxiddismutasa 1; Superoxide Dismutase-1; antioxidancia; Superoxide Dismutase; fenotyp; Oxidative Stress; Partial Pressure; kyslík; Oxygen; oxidační stres; superoxiddismutasa